PERANCANGAN IKLAN HOLDER APPAREL MELALUI MEDIA AUDIO VISUAL - DIMAZ RIZKI FAKHRUR ROZIE, Dr. Syafwandi, M.Sn., Dr. M. Nasrul Kamal, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
Holder apparel clothing line is located on North Sarimas no .1 Sub-district Suka Miskin, Arcamanik , Cicaheum , Bandung. Promotion done by holder apparel less effective so that has not reached its target , so there gap target audience. So far only Holder Apparel promote through the use of website, social networking application or by following some events are located in the area. According Holder Apparel owners, they have not done so effective promotions or interesting as still confused with the choice of a media campaign that will take place. This is because the target audience is expected by the Apparel is the target audience are from all walks of life, such as circles, extreme sport players, musicians, civil society, youth, adults, men, women and others.The aim of this scheme is to introduce and expand the promotional coverage Holder Apparel in order to reach the target audience, particularly in the city of Padang and Bukittinggi. The planning process begins with data collection, observation, interview and documentation. So that the problems that occurred in Holder Apparel can know from the identification of the problem, by using SWOT analysis. This design results in the form of a promotional video that shows impressions of Holder Apparel information about some product visualization and illustration of the concept that in stretcher by the Apparel.Key Word : Advertising Campaign, Audio Visual, Video, Holder Apparel